1989 Action Plan Volume III : Commercial (Agencies) BASAC, DOC & CFA - Bauchi State Integrated Rural Development Authority Planning Department (Bauchi, Nigeria : Bauchi State Integrated Rural Development Authority, 1989)
This is the Bauchi State Integrated Rural Development Authority Planning Department, 1989 Action Plan Volume III, which is focused on commercial agencies like, Bauchi State Agricultural Supply Company (BASAC), Department of Cooperatives (DOC) and Cooperative Financing Agency (CFA).
lje 14/3/19
Arch.
Keywords: Rural development; Road construction; Bauchi State (Nigeria)